Consider CUX1 variants in children with a variation of sex development: a case report and review of the literature - Lynn Tan; Shelley G. Young; Andrew H. Sinclair; Matthew F. Hunter; Katie L. Ayers (BMC, 2024)
Abstract Background The Cut Homeobox 1 (CUX1) gene has been implicated in a number of developmental processes and has recently emerged as an important cause of developmental delay and impaired intellectual development. Individuals with variants in CUX1 have been described with a variety of co-morbidities including variations in sex development (VSD) although these features have not been closely documented. Case presentation The proband is a 14-year-old male who presented with congenital complex hypospadias, neurodevelopmental differences, and subtle dysmorphism. A family history of neurodevelopmental differences and VSD was noted. Microarray testing and whole exome sequencing found the 46,XY proband had a large heterozygous in-frame deletion of exons 4-10 of the CUX1 gene. Conclusions Our review of the literature has revealed that variants in CUX1 are associated with a range of VSD and suggest this gene should be considered in cases where a VSD is noted at birth, especially if there is a familial history of VSD and/or neurodevelopmental differences. Further work is required to fully investigate the role and regulation of CUX1 in sex development.